Oxygenation Effects of Antihypertensive Agents in Intensive Care: A Prospective Comparative Study of Nicardipine and Urapidil - Suard, Florimond; Mombrun, Martin; Fischer, Marc‐Olivier; Hanouz, Jean‐Luc; Decros, Jean‐Baptiste; Derville, Sébastien; Gakuba, Clément; Issa, Ghada; Ménard, Caroline; Chrétien, Basile; Descamps, Richard (Clinical Pharmacology & Therapeutics, 2024)
Acute arterial hypertension within the critical care context may necessitate the administration of intravenous antihypertensive agents. Nicardipine and urapidil are notable for their application in intensive care units. Nonetheless, dihydropyridine calcium channel inhibitors (DCCIs) such as nicardipine are implicated in the impairment of hypoxic pulmonary vasoconstriction, potentially disrupting oxygenation. This study aimed to assess the differences in patient oxygenation when these antihypertensive agents are administered intravenously. This bicentric, prospective, observational investigation spanning five intensive care units evaluated patients requiring intravenous nicardipine or urapidil. Oxygenation data were recorded from the start of therapy until the 12th hour. Comparative analysis was performed between patient groups based on the antihypertensive agent administered, along with subgroup investigations to identify populations with an elevated risk of hypoxemia. From November 2021 to November 2023, 197 patients were included: 98 (50%) were treated with nicardipine, and 99 (50%) were treated with urapidil. Hypoxemia occurred in 97 (49%) patients and was more prevalent in the nicardipine cohort, affecting 65 (66%) patients, as opposed to 32 (32%) patients in the urapidil cohort (RR 2.05, 95% CI [1.48-2.82], P < 0.001). Subgroup analysis revealed a significant association between patients with pulmonary atelectasis (RR 2.30, 95% CI [1.4-3.7], P < 0.001) and obesity (RR 2.7, 95% CI [1.5-4.6], P < 0.001). Considering these findings, cautious consideration of the patient's respiratory status should be exercised when initiating intravenous DCCI treatment. However, given the limitations of this study, a controlled trial on hypertension management in the ICU is needed.